FOSTERING CREATIVE THINKING IN PRESCHOOL CHILDREN THROUGH INNOVATIVE EDUCATIONAL TECHNOLOGIES - Axtamova Mohinur O‘tkir qizi (The Conference Hub, 2025)
This article discusses the concept and essence of creativity, focusing on how creativity develops in preschool children.
Keywords: creativity, philosophy, preschool education, innovation, society.